Bonding technology based on solid porous Ag for large area chips. (15th March 2018) - Chen, Chuantong; Noh, Seungjun; Zhang, Hao; Choe, Chanyang; Jiu, Jinting; Nagao, Shijo; Suganuma, Katsuaki
Abstract: A bonding technology is introduced by using surface polished porous Ag in die-attachment structure. Bonding strength did not change much as the chip size varied from 3 × 3 mm 2 to 15 × 15 mm 2 . This confirms that the technology was not influenced by the chip size, and thus can be used in large area bonding. Bonding mechanism based on stress-induced migration was discussed with the three dimensional finite element analyses. Transmission electron microscopy (TEM) observation further confirmed that single crystal hillocks and Ag particles formed at the bonding interface, bridging the interface together. Graphical abstract: Image 1